Prenatal developmental toxicity of Urtica simensis essential oil in rat embryos and rat fetuses - Bickes Wube; Kaleab Asres; Samuel Woldekidan; Abiy Abebe; Yonas Girma; Girma Seyoum (PLoS ONE, 2025)
Pregnant women inhaled fresh U. simensis steam vapor to fumigate their bodies, and boiled it for tea. However, the safety of this practice during pregnancy has not yet been reported. This study aimed to evaluate the prenatal developmental toxicity of U.simensis essential oil in rat embryos and fetuses. The essential oil was extracted through hydrodistillation from aerial parts of U.simensis. One hundred pregnant rats were randomly assigned to five groups (20 rats per group). Groups I to III were administered oral doses of 250, 500, and 1000 mg/kg of U.simensis essential oil. Groups IV and V were used as pair-fed and ad libitum controls, respectively. The developing embryos and fetuses were retrieved on 12 and 20 days of gestation, respectively. Embryos were evaluated for growth and developmental delays. Fetuses were evaluated for external, skeletal, and visceral abnormalities. Oral doses of 250 and 500 mg/kg of U.simensis essential oil had no observed adverse effects in both rat embryos and rat fetuses. However, somite numbers and morphological scores were significantly decreased in gravid rats treated with 1000 mg/kg of essential oil. Embryonic developments of the caudal neural tube and forebrain were significantly delayed in pregnant dams administered 1000 mg/kg of essential oil. Crown-rump length and fetal weight were significantly decreased in gravid rats given 1000 mg/kg of essential oil. Gravid rats received 1000 mg/kg of essential oil also revealed a significant increase in fetal resorption. In conclusion, high-dose oral administration of U.simensis essential oil revealed detrimental effects in both rat embryos and fetuses. Therefore, pregnant women should be informed the potential risks associated with the nutraceutical use of U.simensis during pregnancy.